Penerapan Pendidikan Demokrasi Substantif bagi Siswa/I Kelas XII 5 SMAN 35 Jakarta dalam Rangka Pemilihan Kepala Daerah untuk Mewujudkan Pemerintahan yang Ideal - Rosyidah, Najwa; Putra, M. Aliev Andika; Qowy, Aqila Hifdzil; Ahmad, Nisa Auliya; Lewoleba, Kayus Kayowuan; S, Subakdi; S, Suprima (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
In order to welcome the election of regional heads and to realize elections based on reason or ratio by critically examining the thoughts or vision and mission of the candidate pairs so that substantive democratic values can be achieved. Substantive democracy itself is when a government can realize the wishes of the people in a country, where the people themselves have the highest sovereignty in a democracy. Class This socialization activity takes the form of providing material about elections and regional elections, then there is a question and answer session and a test after providing the material to see whether the students have understood the content of the material or not. This socialization activity aims to enable students to choose leaders critically and provide an understanding of elections and regional elections. It is hoped that this activity will enable the younger generation to actively participate in politics and also create an ideal government.